Development of a tension pneumomediastinum during mechanical ventilation of a young Irish Wolfhound. Issue 3 (8th March 2020) - Zersen, Kristin M.; Haraschak, Jenica L.; Sullivan, Lauren A.
Abstract: Objective: To report the development of a tension pneumomediastinum during mechanical ventilation of a young Irish Wolfhound with aspiration pneumonia. Case Summary: A 9‐month‐old intact female Irish Wolfhound was presented for clinical signs consistent with aspiration pneumonia. Evaluation of her pedigree and clinical signs prompted suspicion of Irish Wolfhound rhinitis bronchopneumonia syndrome as a contributing factor. Despite supportive care for bronchopneumonia, progressive hypoxemia and increased work of breathing required mechanical ventilation (MV). Development of a pneumothorax 36 hours after initiation of MV necessitated bilateral thoracostomy tubes. Cardiovascular decline persisted despite resolution of the pneumothorax and 1 hour later the dog was humanely euthanized. On necropsy, severe pneumomediastinum was identified without other evidence of barotrauma. Necropsy results suggested tension pneumomediastinum as the cause of pneumothorax and cardiovascular deterioration. New or Unique Information Provided: Pneumomediastinum has not been described in dogs receiving MV. This case highlights the importance of rapid detection of pneumomediastinum during MV, as the complication can quickly become life‐threatening.